Outcomes of Percutaneous Transluminal Angioplasty for Central Vein Stenosis in Hemodialysis: A Literature Review - Ibrahim, Hilman; Muradi, Akhmadu; Limianto, Eka A (The New Ropanasuri Journal of Surgery, 2021)
Percutaneous transluminal angioplasty (PTA) is the mainstay treatment for central vein stenosis. However, the recurrent rate of the stenotic lesion after PTA remains high. Thus, we ran a review found on some databases. Out of thirteen articles, five articles were eligible and reviewed. Drug-coated balloon angioplasty, plain old balloon angioplasty, percutaneous transluminal angioplasty, and stenting angioplasty were discussed regarding the outcomes with a focus on interest to prevent the stenosis.